135 Evolution of a Study of Bilateral Prefrontal Transcranial Magnetic Stimulation (TMS) to Treat the Symptoms of Mild TBI (mTBI) and PTSD. (April 2020) - Garland, Jared S; Jaskot, Emilia-Marie; Taylor, Jerika; Buccellato, Kiara; Atwal, Navneet; Pasquina, Paul F
Abstract : Disclaimer: The views expressed in this abstract are those of the authors and do not reflect the official policy of the Department of Army/Navy/Air Force, Department of Defense, or U.S. Government. Background: Traumatic brain injuries (TBIs) have affected nearly 380, 000 service members since 2000. Comorbid posttraumatic stress disorder (PTSD) may result from and/or exacerbate sequelae of mild TBI (mTBI) and is suspected to affect up to 65% of service members with TBI. Conventional treatments for mTBI/PTSD symptoms have limited efficacy and are associated with undesirable side effects. Repetitive transcranial magnetic stimulation (rTMS) has shown promise in treating PTSD symptoms and been identified as a potential mTBI therapy, but is untested as a therapy for comorbid mTBI/PTSD. Methods: This double-blinded, prospective randomized, sham-controlled study consists of 30 treatment sessions 5 weeks of daily sessions followed by a two week taper of 3 and 2 sessions, respectively. Sessions consist of 3500 pulses administered to the left dorsolateral prefrontal cortex (dlPFC) at 10 Hz and 1500 pulses to the right dlPFC at 1 Hz. Approximately 60-80 participants will be randomized to receive active or sham rTMS. Primary outcome measures are the Posttraumatic Checklist 5 and the Rivermead Post-Concussion Questionnaire. Results: The study is ongoing, and 26 participants have been recruited to date. All patients were formally diagnosed with mTBI and reported moderate to severe PTSD symptoms. Preliminary data show no participants have withdrawn due to intolerability or indicated intolerability, despite the presence of minor discomforts such as headache. The majority of participants have been able to rest quietly or sleep during sessions, indicating high tolerability. Reported pain levels are low, with average ratings of 2.84/10.00 by week 2. One limitation was a high dropout rate. Conclusions: This study aims to provide guidance as to whether rTMS is an efficacious therapy for comorbid mTBI/PTSD. Preliminary data indicates it to be a tolerable and safe therapy. Future research should consider decreasing the demand of the study on patients schedules, and performing a comparison to other mTBI/PTSD treatments to determine what treatment is more efficacious.